Establishing criteria for landfill siting in the Philippines using fuzzy multi criteria decision analysis - Regalado, Timothy Justine V.
According to the National Solid Waste Management (NSWMC), as of 2015, the Philippines has a total of 1002 landfills, 560 of which are open dumpsites, 308 are controlled disposal facilities and 134 are sanitary landfills. Only 2 of these landfills, however, are located in Metro Manila, considering the fact that it has the most amount of wastes produced according to them as well. With Payatas Dumpsite being shut down, there remains only one active landfill within NCR, namely Navotas Landfill. Even though wastes can be transferred to nearby landfills, it would still cost more due to transportation and collection. The necessity for a new landfill is high, considering as well that the existing landfills around the country are almost full. This is where landfill siting comes in, however, conflict may arise when analyzing each factor for landfill siting. All factors to be considered in landfill siting is stated in the Implementing Rules and Regulations of Republic Act 9003. In this study, the Fuzzy Multi Criteria Decision Analysis was used to rank the factors to determine which factors should of highest priorities. This study aims to advise and lessen the confusion as to which sites should be chosen when landfill siting is performed in the future. A survey was conducted, which were answered by experts on Solid Waste Management, Environmental Engineering, Geotechnical Engineering and Environmental Planning. When processed and analyzed, the top three factors were determined to be depth of groundwater, distance from perennial streams or rivers and location from schools and residential areas.